2016
DOI: 10.1038/srep32937
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine regulates activity of lateral habenula neurons via presynaptic and postsynaptic mechanisms

Abstract: There is much interest in brain regions that drive nicotine intake in smokers. Interestingly, both the rewarding and aversive effects of nicotine are probably critical for sustaining nicotine addiction. The medial and lateral habenular (LHb) nuclei play important roles in processing aversion, and recent work has focused on the critical involvement of the LHb in encoding and responding to aversive stimuli. Several neurotransmitter systems are implicated in nicotine’s actions, but very little is known about how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…Nicotine increases LHb neuron activity when acutely administered in vivo [26], depolarizing directly LHb neurons via postsynaptic α6-containing (α6*) nAChRs but also modulating GABA and GLU input onto LHb neurons [40]. The involvement of 5-HT inputs on the nicotine effect in the LHb is also probable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine increases LHb neuron activity when acutely administered in vivo [26], depolarizing directly LHb neurons via postsynaptic α6-containing (α6*) nAChRs but also modulating GABA and GLU input onto LHb neurons [40]. The involvement of 5-HT inputs on the nicotine effect in the LHb is also probable.…”
Section: Discussionmentioning
confidence: 99%
“…through the lateral tail vein 640 µg/kg cumulative doses of TCB-2 or its vehicle. A total of eight doses (5,5,10,20,40,80,160 and 320 µg/kg), each dissolved in 100 µL of the vehicle were given at two-minute intervals.…”
Section: Drugs and Pharmacological Treatmentsmentioning
confidence: 99%
“…Changes in habenular nicotinic responses were not significant when broken out into components sensitive to lower and higher concentrations of ACh (LS and HS, respectively). Although current methods evaluate presynaptic responses, recently published work shows nicotine activates GABAergic inputs to the LHb, which then excite GABAergic neurons in the rostromedial tegmental nucleus (RMTg) that then in turn inhibit midbrain dopaminergic neurons . The data are interesting in light of current studies showing changes persisting in presynaptic dopamine release.…”
Section: Discussionmentioning
confidence: 99%
“…Motivation to self‐administer drugs of abuse, including nicotine, despite their noxious effects is mediated by adaptations of DA transmission specifically linked to cholinergic afferents that encode reinforcing stimuli . In what may serve as a “balance” to the rewarding properties of nicotine, the habenula‐interpeduncular nucleus (Hb‐IPN) pathway appears to play a role in aversive responses to nicotine . A clear role for this pathway in aversion is illustrated in Fowler et al who showed that α5 nicotinic subunit KO mice continue nicotine self‐administration at doses that wild‐type (WT) mice find aversive.…”
mentioning
confidence: 99%
“…Of note, though nicotine is relatively selective for α4β2 nAChRs, it does have affinity for other subtypes, including α5-and α6-containing, as well as α7 nAChRs, which can also be present in the RVM [237,246,248,249]. Others investigating the actions of nicotine have suggested that its effects may be mediated partially [253,323] or only minimally by α4β2 nAChRs [324]. While actions at non-nAChRs are less likely, a few studies have shown functional activity of nicotine at 5-HT 3 Rs and NMDA receptors [325].…”
Section: The Effects Of Nicotine In the Rvm In The Presence Of Receptmentioning
confidence: 99%